Adsorption of Hg (II) from aqueous solution using carboxymethyl glucomannan derivative - Thi Dong, Nguyen; Tien An, Nguyen; Truong Thien, Do; Le Dung, Pham (Vietnam Journal of Science and Technology, 2017)
Carboxymethyl glucomannan derivative (CMG) with the degree of substitution of 0.697 was synthesized from the reaction of monochloroacetic acid (MCA) with glucomannan paeoniiifolius (GP) at 60 C, pH10 for 3 h. Its structural characteristics were proven by nuclear magnetic resonance (NMR). The resulting derivative was used to adsorb Hg2+ ion from aqueous solutions. The effects of pH, initial concentration of metal ions and contact time on CMG’s adsorption behaviors were also investigated. The results have shown that the optimal pH for adsorption was about 6.5; the adsorption capacity rapidly reached equilibrium within 40 minutes; the maximum adsorption capacity of CMG for Hg2+ ion was 615 mg/g.